2019
DOI: 10.1177/1071181319631252
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Algorithm for Automatically Assessing Lifting Risk Factors Using Inertial Measurement Units

Abstract: The objective of this study was to develop an algorithm for automatically processing data collected with inertial measurement unit (IMU) wearable devices to measure lifting risk factors for low back disorders. Five IMU sensors attached to five body segments were used for developing the algorithm. The algorithm consists of two modules running in parallel for detecting the beginning and ending of a lifting event as well as the vertical height (V) of the object lifted by two hands and the horizontal (H) distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Moreover, machine learning (ML) algorithms are gaining popularity in the ergonomic field for biomechanical risk assessment by means of data acquired by wearable inertial systems. Several publications have appeared in recent years documenting several strategies [ 27 , 28 , 29 ]. IMU systems, which incorporate machine learning into their data analysis pathways, have been found effective in automated exercise detection and in classifying movement quality across a range of lower limb exercises, including lifting, despite studies in this field having so far involved few samples [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, machine learning (ML) algorithms are gaining popularity in the ergonomic field for biomechanical risk assessment by means of data acquired by wearable inertial systems. Several publications have appeared in recent years documenting several strategies [ 27 , 28 , 29 ]. IMU systems, which incorporate machine learning into their data analysis pathways, have been found effective in automated exercise detection and in classifying movement quality across a range of lower limb exercises, including lifting, despite studies in this field having so far involved few samples [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the cases where the lift detection algorithm mislabeled a start or end have very poor parameter estimation results. To counter this, it could be possible to use additional features, such as inertial coupling between the hands [24], as a redundant check to make sure that a lift is actually occurring between the detected start and end times. If one is not, the algorithm can strategically search for better times.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…The biggest challenge in developing the algorithms for real-time would be identifying the start and end of a lift amidst a continuous stream of data. Lu et al demonstrated one plausible method for accomplishing this using a sliding pattern recognition window [24]. Once that problem is solved, the analysis could be done the same way it is done offline.…”
Section: Conversion To Real-timementioning
confidence: 99%
See 1 more Smart Citation
“…The equations below were used for estimating the V and H variables. The development of the algorithm is described in detail in a separate proceeding paper (Lu et al, 2019).…”
Section: Algorithm For Processing Imu Datamentioning
confidence: 99%